Effect of oral hygiene education and motivation on removable partial denture wearers: longitudinal study - Ribeiro, Daniela Garcia [UNESP]; Pavarina, Ana Claudia [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Machado, Ana Lucia [UNESP]; Jorge, Janaina Habib [UNESP]; Nordi Sasso Garcia, Patricia Petromilli [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
The purpose of this study was to determine the effect of two different preventive oral hygiene education and motivation programmes on the plaque and gingival index, as well as denture hygiene of patients provided with removable partial denture (RPD) during a 12-month follow-up.A total of 53 partially edentulous patients were recruited for this study. The presence or absence of plaque and gingival bleeding by gentle probing was scored on all tooth surfaces at the preliminary visit. The plaque and gingival indexes were measured using the Loe index. Following treatment, the patients were randomly divided into three groups. In Control Group I, subjects were instructed to continue their personal oral hygiene routine. In Group II, participants were given verbal instructions and a self-educational manual on oral hygiene without illustrations. In Group III, oral hygiene guidance was delivered using a combination of verbal instructions and a self-teaching manual. To evaluate the effect of the different modes of instruction, the presence or absence of plaque and gingival bleeding was scored on all tooth surfaces (day zero examination) and re-examined 7, 15 and 30 days, 3, 6 and 12 months following RPD placement. The state of denture hygiene was evaluated 7, 15 and 30 days and 3, 6 and 12 months following rehabilitation. Parametric statistics was applied to dental plaque and gingival indexes. For accumulation of plaque and calculus on the RPD, non-parametric statistic was applied.The frequency of plaque found during the preliminary visit was higher than that found in the other periods. With regard to gingival index, significant difference was found between the preliminary visit examination and other periods. There was a significant difference in the plaque accumulation on the denture surface between groups I and III.The different methods of oral hygiene instruction used in this study indicate that the type of education was not of significant importance.
Keywords: denture; partial; removable; oral hygiene; education; dental